Ian Thorpe at 75 m of His World-record 400 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Ian Thorpe at 75 m of his World-record 400 m race at the 1999 Pan Pacific Championships in Sydney . There are only minor differences in technique between the form shown here at 75 m and the form exhibited at 375 m. The race was negatively split at 200 meters. During the race, the fifth lap was covered faster than most other 50-m sections as Ian Thorpe broke from the field. The most obvious technique difference, and it is only a minor one, occurs with the effective propulsion phase of the left-arm pull. It starts earlier in the stroke than at 375 m. That earlier start also occurs with the recovering arm not as far through its phase as at the latter stage of the race.